2011
DOI: 10.1124/dmd.111.039206
|View full text |Cite
|
Sign up to set email alerts
|

Oral Absorption of Clarithromycin Is Nearly Abolished by Chronic Comedication of Rifampicin in Foals

Abstract: ABSTRACT:The delivery of clarithromycin (CRL) to its site of action in bronchial/alveolar epithelial cells (EC), bronchial epithelial lining fluid (ELF), and bronchoalveolar lavage cells (BALC) may be influenced by CYP3A4 and the drug transporters, ATP-binding cassette (ABC) B1 and ABCC2 and organic anion-transporting polypeptides (OATPs), which can be modulated and/or up-regulated via the nuclear pregnane X receptor (PXR) by rifampicin (RIF). Therefore, we evaluated the disposition and pulmonary distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 39 publications
(54 reference statements)
5
75
1
Order By: Relevance
“…We and others found that plasma exposure with 14OH-CLR (AUC and trough levels) was almost not influenced by RIF, after either short-term or long-term coadministration, although CLR absorption was dramatically reduced (Wallace et al, 1995;Taki et al, 2007;Peters et al, 2011); the lower AUC 0 -12h in our chronic study is explained by a decreased half-life of 14OH-CLR after induction of its terminal metabolism (Ferrero et al, 1990). It might be that the proximal intestine is the major site of CLR hydroxylation in horses, where CYP3A metabolic activity is highly expressed (Tydén et al, 2004).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We and others found that plasma exposure with 14OH-CLR (AUC and trough levels) was almost not influenced by RIF, after either short-term or long-term coadministration, although CLR absorption was dramatically reduced (Wallace et al, 1995;Taki et al, 2007;Peters et al, 2011); the lower AUC 0 -12h in our chronic study is explained by a decreased half-life of 14OH-CLR after induction of its terminal metabolism (Ferrero et al, 1990). It might be that the proximal intestine is the major site of CLR hydroxylation in horses, where CYP3A metabolic activity is highly expressed (Tydén et al, 2004).…”
Section: Discussionmentioning
confidence: 61%
“…Thirdly, the terminal elimination of 14OH-CLR by cytochrome P450 enzymes (N-demethylation and hydroxylation) was unchanged after short-term coadministration of RIF (7.28 Ϯ 1.35 versus 6.60 Ϯ 1.76 h; n.s.) but was significantly decreased after long-term treatment (8.11 Ϯ 1.61 versus 5.10 Ϯ 0.88 h; p Ͻ 0.05) (Suzuki et al, 2003;Peters et al, 2011). Therefore, the increased proportion of 14OH-CLR exposure (AUC 0 -12h ) relative to the AUC of total CLR (0.52 Ϯ 0.13 versus 0.21 Ϯ 0.06, p Ͻ 0.01) is most likely not caused by induction of CYP3A4 hydroxylation of CLR (Suzuki et al, 2003), and induction of presystemic metabolism of CLR is not the major reason for the Ͼ70% decrease in bioavailability (alternative reasons are noted in the discussion below).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLR is often selected over other macrolides because of its greater in vitro activity against R. equi (6) and because a retrospective study in foals suggests that, in combination therapy with RIF, CLR is more effective than other macrolides (8). However, in both people and foals, concurrent administration of RIF considerably reduces CLR concentrations compared to concentrations achieved with CLR monotherapy (14)(15)(16). This has raised the question of whether administration of RIF in addition to CLR is necessary, or even advisable, for the treatment of infections caused by R. equi.…”
mentioning
confidence: 99%
“…All mice were weighed every 48 h. Treatments were RIF alone (10 mg/kg of body weight), CLR alone (25 mg/kg), combination therapy with CLR-RIF (25 mg/kg and 10 mg/kg, respectively), and 0.9% NaCl (control). The dosages and dosing intervals used were those likely to result in plasma drug concentrations similar to those achieved with the use of these antimicrobial agents in combination in horses and people (14,15,20,21). All treatments were diluted to an injection volume of 0.1 ml.…”
mentioning
confidence: 99%